Implementation of Scaffolding in Project Based Learning Model to Improve Skills of Science Process in Buffer Solution Material - Tri Haryati; Diah Riski Gusti; Muhammad Haris Effendi Hasibuan; Muhammad Rusdi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Dynamic assessment, which is supported by scaffolding, consists of questioning, prompting, cueing, and explaining. Scaffolding is considered as an effort to overcome learning problems which present in the concept of buffer solution as well as in the Project-based Learning, which aims to improve students' science process skills. This study aims to investigate the implementation of scaffolding to improve students' science process skills about the concept of buffer solution. Data were collected using in-depth interviews and analyzed using the Delphi technique. Based on the results of the analysis, it can be seen that the ideal scaffolding widely used was the questioning and the prompting. This was because the students only needed to be guided to solve the problems using the most appropriate assistance to overcome the issues. Therefore, it can be concluded that the implementation of the scaffolding was able to help the students to overcome the problems that occur during the learning process. The implementation was also able to improve the students' understanding and skills of the science process about the concept of buffer solution.